2016
DOI: 10.18632/oncotarget.9061
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of PD-L1 and p-AKT is associated with poor prognosis in diffuse large B-cell lymphoma via PD-1/PD-L1 axis activating intracellular AKT/mTOR pathway in tumor cells

Abstract: Programmed death-1 (PD-1) /programmed death-ligand 1 (PD-L1) engagement usually leads to diminished antitumor T-cell responses, which mediates the immune escape of tumor cells. However, little is known whether PD-1/PD-L1 could directly activates intracellular oncogenic signaling pathways in tumor cells. The purpose of this study is to investigate whether intracellular AKT/mTOR signaling could be directly activated by PD-1/PD-L1 during the malignant progression in diffuse large B-cell lymphoma (DLBCL). Detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 55 publications
(48 reference statements)
3
61
0
9
Order By: Relevance
“…Interestingly, Dong et al found that the AKT/mTOR pathway was significantly activated in DLBCL cell lines upon a treatment with human recombinant PD1/Fc for 24 h and 48 h [21]. This finding indicates that the ligand engagement may also deliver the reverse signaling to tumor cells themselves apart from the forward signals to suppress the immune response through PD-1, which is consistent with the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, Dong et al found that the AKT/mTOR pathway was significantly activated in DLBCL cell lines upon a treatment with human recombinant PD1/Fc for 24 h and 48 h [21]. This finding indicates that the ligand engagement may also deliver the reverse signaling to tumor cells themselves apart from the forward signals to suppress the immune response through PD-1, which is consistent with the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, several studies also indicated that CD274 may serve as a “receptor” to deliver “reverse” signaling [1921]. For example, Dong et al discovered that total PD-L1 and membrane PD-L1 protein were overexpressed in some DLBCL cells, and the AKT/mTOR pathway was activated by PD-1/Fc stimulation, which indicated that PD-1/PD-L1 directly activated the intracellular oncogenic signaling pathway in tumor cells [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erste Ergebnisse haben additive Effekte einer Bestrahlung und CheckpointModifikation gezeigt, und es wird interessant sein, ob die Kombination mit verringerten Nebenwirkungen und eine erhöh-ten Wirksamkeit verbunden ist [77]. Noch interessanter könnte ein anderer kombinierter Ansatz sein, wie etwa die Kombination von Checkpoint-Inhibitoren mit biologikabasierten Therapien, die die Immun-Mikroumgebung des Tumors verändern, wie IDO(Indoleamin-2,3-dioxygenase)-Hemmer, die beim nicht kleinzelligen Bronchialkarzinom (NSCLC, non-small cell lung cancer) zusammen mit Pembrolizumab erfolgversprechende Ergebnisse gezeigt haben [78]; außerdem die Kombination mit Arzneimitteln, die JAK2 oder andere Kinasen [59,79], die bekanntermaßen an der T-Zell-Regulation beteiligt sind oder die in der Biologie des jeweiligen Lymphoms eine spezielle Rolle spielen, verändern [80]. Immunmodulatorische Arzneimittel wie Lenalidomid, das sich bei zahlreichen Lymphom-Entitäten als wirksam erwiesen hat, gelten als attraktiver Kombinationspartner.…”
Section: Potenzielle Kombinationstherapienunclassified
“…Early results have shown additive effects of radiation and checkpoint modification -it will be interesting to see if this could be helpful in reducing side effects while increasing efficacy [77]. Even more interesting could be the approach to combine checkpoint-inhibiting drugs with biology-based approaches in order to modify the immune microenvironment, like indoleamine-2,3-dioxygenase (IDO) inhibitors, which have shown promising results in combination with pembrolizumab in non-small cell lung cancer (NSCLC) [78], or drugs that modify JAK2 or other kinases [59,79] known to be involved in T cell regulation or to play a distinct role in the biology of the specific lymphoma [80]. Immunomodulatory drugs like lenalidomide, which has been shown to be effective in many lymphoma entities, are considered to be an attractive partner; however, unforeseen toxicities of these combinations have been described recently.…”
Section: Potential Combinationsmentioning
confidence: 99%